Gender Norm Conflict and Marital Outcomes - Francisca M. Antman; Priti Kalsi; Soohyung Lee (Institute of Labor Economics (IZA), 2021)
We investigate the impact of male-female conflict over gender norms on marital outcomes. As marriage requires mutual agreement regarding the role of husband and wife, we hypothesize that a person who is less likely to encounter a potential mate with similar gender norms will face a lower chance of marrying. Even if two parties marry despite a difference in gender norms, their marriage may be more vulnerable to external shocks, making divorce more likely relative to their counterparts without gender norm conflict. Finally, we predict that in the presence of gender norm conflict, high-skilled individuals may be less likely to get or stay married relative to low-skilled individuals, as the former group faces better outside options. Estimates from an analysis of U.S. marriage markets differentiated by birth cohort, state, race, and skill level, support our theoretical predictions. Additional extensions explore heterogeneous effects and additional outcomes such as the presence of children in the household.
Keywords: J12; J16; J24; 330; skill gap; divorce; social norms; marriage; gender